The relative importance of social responsibility in determining organizational effectiveness: Managers from two service industries - Kraft, Kenneth L. (Journal of business ethics, 1991)
This paper investigates the relative importance of social responsibility criteria in determining organizational effectiveness as seen by managers of two service industries. The Organizational Effectiveness Menu (Kraft and Jauch, 1988) was used as a questionnaire with a sample of 53 firms. The conclusion is that while managers view ethical conduct as among the most important determinants of organizational effectiveness, numerous other social responsibility criteria are assigned relatively low priority. A question remains as to what managers will actually do when faced with limited resources.